Teaching to the distance education: approaching about the professional profile - Nunes, Andrea Karla Ferreira; Oliveira, Alice Virginia Brito de; Sabino, Rosimeri Ferraz (Universidade Estadual de Campinas, 2019)
This work aimed to delimit the distinctive elements of teaching representation for distance education, based on the analysis of the legislation on teacher education and the concept of politeaching. It was considered the constitution of the teaching profile to act in this modality, before the impositions of the new socio-educational context and the challenges for the teachers, mainly, in what concerns the communication and the interaction that involve the process of teaching and learning. The methodology adopted was bibliographic and documentary research. The results showed that the teacher in EaD, among the various attributes that identify, must be able to share knowledge, manage groups, be dialogical, besides being empathetic, ethical, interpersonal competence and willingness to new learning.